Analysis of Suhrawardī’s Opinion on the Issue of General Principles and Mullā Ṣadrā’s Confrontation - Muhammad Hosseinzadeh (آموزه‌‌های فلسفه اسلامي)
Muslim philosophers have been influenced by the views of ancient Greek philosophers in the issue of generality (generic) and partiality, so that the essence of the views presented in the Islamic era can be seen in the opinions of Plato and Aristotle. Avicenna, like Aristotle, has denied the theory of Forms (theory of Ideas) and rejected Plato’s view about the general and partial issue. Unlike Avicenna, Suhrawardī has accepted the Platonic theory of Forms, but he has denied the Platonic generality in the issue of generality (generic) and partiality and has had a common opinion in explaining of “generic” (Arabic: کلّی) with Aristotle and Avicenna, which means that he, like Avicenna, considers generality to be the same of mental concept as independently subsistent. Of course, Shaikh al-ʿIshraq (Master of Illumination) has opposed Avicenna in some minor aspects of this issue and has presented innovations. This article has explained Suhrawardī’s point of view on the issue of generality (generic) and partiality by an analytical-descriptive method and studied the reason of his tendency to Peripatetic explanation of the “generic”. Suhrawardī’s critiques of Sinavi’s approach have also been explained in this analytical study, and their impact on Mullā Ṣadrā’s critique on Peripatetic’s theory has been shown. Also, Mullā Ṣadrā’s encounter with Suhrawardī’s view on the issue of generality (generic) has been analyzed.